Pengembangan Buku Panduan Guru Dalam Mengoptimalkan Artificial Intelligence (AI) Untuk Menunjang Pembelajaran - Asidiqi, Deby Fauzi; Ginanjar, Ajeng; Adiputra, Dede Kurnia; Suwarno (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Education is a major milestone in building the foundation of a nation's excellence. In the digital era and the industrial revolution 4.0, the application of artificial intelligence (AI) technology is becoming increasingly important in improving the effectiveness of learning. This study aims to develop an instructional guide for teachers in utilizing AI optimally in the context of learning. The method used in this study is based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model. The analysis stage will consider the needs of teachers and the potential use of AI in the context of learning. Furthermore, the design stage will lead to the creation of an instructional guide based on pedagogical principles and AI technological capabilities. Furthermore, the design stage will lead to the creation of an instructional guide based on pedagogical principles and AI technological capabilities. This study aims to develop a teacher's guidebook in optimizing the use of Artificial Intelligence (AI) to support the learning process. The methodology used is ADDIE, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of the analysis show that the majority of teachers feel they lack knowledge about AI and its applications in education. This guidebook is designed to provide theoretical understanding and practical applications of AI in various subjects.